2016
DOI: 10.17060/ijodaep.2014.n1.v5.649
|View full text |Cite
|
Sign up to set email alerts
|

Programa De Intervención Para La Mejora De Las Creencias De Autoeficacia en Las Clases De Ciencias Intervention Program to Improve the Self-Efficacy Beliefs in Science Classes

Abstract: This paper offers the description about a intervention program designed as a result of a study about the affective domain aroused in prospective Primary teachers in their initial teacher education during their science classes, with the result of negative self-efficacy beliefs. The aim is an improving of the self-efficacy beliefs in their science teaching practices, as of some activities in three timeframes: before, during and after their practices in the schools. The total sample was 11 prospective Primary tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Research on the science education has resulted in the elaboration of some science teacher training programs aimed at developing metacognitive capabilities (Brígido et al., 2014; Copello and Sanmartí, 2001; García and Orozco, 2008; Gunstone and Northfield, 1994; White and Mitchell, 1994). These skills favour the recognition of possible causes of difficulties or problems when teaching, and also facilitate the self-regulation of changes in affective factors within the process of teaching science and the development of new activities, materials, and education proposals (Powell and Anderson, 2002; Sassi et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the science education has resulted in the elaboration of some science teacher training programs aimed at developing metacognitive capabilities (Brígido et al., 2014; Copello and Sanmartí, 2001; García and Orozco, 2008; Gunstone and Northfield, 1994; White and Mitchell, 1994). These skills favour the recognition of possible causes of difficulties or problems when teaching, and also facilitate the self-regulation of changes in affective factors within the process of teaching science and the development of new activities, materials, and education proposals (Powell and Anderson, 2002; Sassi et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with the statements of other authors [104,105] who indicated that trainee teachers' beliefs are often projected onto their future teaching in the primary classroom. If a teacher feels unprepared to teach science, this will contribute to fostering negative attitudes towards science learning in future students [86]. Additionally, based on the results obtained in the research with respect to the didactic interventions developed, we can conclude that the use of hyper-realistic simulations and the STEM experiences designed promote the acquisition of scientific competence in the trainee teacher combats the misconceptions found in them and significantly increases the learning of optics with respect to more traditional teaching.…”
Section: Acceptedmentioning
confidence: 83%
“…In addition, the aim was to analyze the level of self-efficacy of prospective primary school teachers in teaching content about light and color. For this purpose, a questionnaire was designed based on previous research [15,86,87]. The questionnaire, on teaching selfefficacy on light and color, consisted of 28 items that were formulated based on the optical contents and activities to be developed in the classroom of the fifth and sixth grades of primary education.…”
Section: Measuring Instrumentmentioning
confidence: 99%
“…Woodbury y Gess-Newsome ( 2002), Jay y Johnson (2002), Lotter y Miller (2017) y más recientemente Vázquez-Bernal et al (2019) plantean que el modo en que el profesorado piensa está determinado por la interde- pendencia de las facetas del contexto general en el que llevan a cabo su práctica docente, así como en la forma y la profundidad en que la reflexión se enfoca. Por otro lado, dado que la propia conducta y experiencia vital de un investigador influirá en sus concepciones (Schraw y Olafson, 2003) parece fundamental intentar cuantificar las valoraciones subjetivas, en un intento, sólo eso, de acercar la teoría a la investigación educativa ) con la idea de autoeficacia de fondo (Brígido et al, 2014). Aunque aplicable al caso del cambio de modelo educativo, parece oportuno citar a Reza (2019), autora que plantea el interés en analizar la variedad de sentimientos y acciones que dicho cambio produce en los docentes, en cuanto a curiosidad, incertidumbres, investigación y estudio para su adecuado manejo y dominio, y los discentes, en cuanto a las estrategias y actividades que realizan bajo la planificación, dirección y guía del docente, para que sean adecuadas y conduzcan a los propósitos que se pretenden, lo cual lleva a la práctica reflexiva permanente que tiene como objetivo la transformación del ejercicio docente para ofrecer al alumnado un servicio de mayor calidad.…”
Section: Introductionunclassified